PHOTOCHEMICAL RING-OPENING AND EXPANSION REACTION OF 2,4-DINEOPENTYL-1,1,3-TRIPHENYL-3-VINYL-1,3-DISILACYCLOBUTANE - YOO, BR; LEE, ME; JUNG, IN (AMER CHEMICAL SOC, 1992)
Photolysis of 2,4-dineopentyl-1,1,3-triphenyl-3-vinyl-1,3-disilacyclobutane (1) in the presence of methanol and methoxytrimethylsilane gives three major products, ring-opened alkenylsilanes, trapping products of silaethenes, and six-membered-ring products. The results are consistent with the initial formation of 1,4-biradical intermediates which undergo three competing reactions: intramolecular hydrogen abstraction leading to alkenylsilanes, fragmentation to silaethenes, and ring closure to six-membered-ring silenes. This is the first evidence for the generation of a six-membered-ring silene by the novel ring-closure reaction involving the vinyl group on silicon.
Keywords: TERT-BUTYLLITHIUM; SILAHETEROCYCLES